Cooperative versus Coercive Social Power in Adolescence - Volk, Anthony A; Dane, Andrew V; Craig, Wendy; Spadafora, Natalie; Andrews, Naomi C Z; Vitoroulis, Irene; Farrell, Ann H; Lambe, Laura J (Advances in Social Sciences Research Journal, 2025)
There are two fundamental forms of social power: cooperative (where individuals mutually benefit) and coercive (where the more powerful gains at the expense of the other). Each is composed of two separate aspects: power holding (e.g., being popular) and power-enhancing(e.g., using force). Research has generally studied these two forms of social power in a single measure and without consideration of their combined effect nor examined their combined influence or associations with peer reactions. We therefore used a measure that captured both aspects and forms of adolescent social power as well as to determine their associations with positive and aggressive peer responses. Based on a sample of 559 adolescents, our confirmatory factor analysis demonstrated that adolescents viewed each form of social power as being distinct from each other and composed of both power-holding and power-enhancing aspects. We then ran structural equation models that showed cooperative social power was associated with numerous positive peer responses (e.g., friendship, respect) while coercive social power was associated with fewer positive peer responses (e.g., attractiveness, support in a conflict) as well as more aggressive peer responses (e.g., bullying and victimization). Our longitudinal data (collected 6 months later) showed even clearer separation of these associations of these two forms of social power. Overall, our results suggest that researchers should use measures that capture both aspects of social power and that each form of social power has a distinct pattern of associations with peer responses.